BRAND IMAGE DAN PROMOSI DIGITAL DALAM MEMBENTUK KEPUTUSAN PEMBELIAN SKINCARE SKINTIFIC KONSUMEN SUKABUMI - Lisnawati, Euis; Pramadista, Angga; Kusmawan, Engkus (PT. ABIG RIZKY PUBLISHER, 2025)
This study aims to determine the influence of Brand Image and Digital Promotion on consumer purchase decisions of Skintific skincare products at Kawaidollshop Sukabumi City. Using a quantitative causal associative approach, the research involved 100 respondents who are Skintific consumers at Kawaidollshop. Primary data were collected through a closed Likert-scale questionnaire. Data analysis included instrument quality testing, analysis prerequisite testing, multiple linear regression, coefficient of determination, as well as t-test (partial) and F-test (simultaneous). The results indicate that Brand Image has a positive and significant partial effect on purchase decisions (Sig. 0.000 < 0.05; t-count 7.407 > t-table 1.984). Digital Promotion also has a positive and significant partial effect on purchase decisions (Sig. 0.000 < 0.05; t-count 3.970 > t-table 1.984). Simultaneously, Brand Image and Digital Promotion significantly influence purchase decisions (Sig. 0.000 < 0.05; F-count 1031.045 > F-table 3.09). The variation in purchase decisions is explained by Brand Image and Digital Promotion by 95.4% (Adjusted R Square = 0.954). The implications of this study suggest continuous improvement in Brand Image and digital promotion strategies at Kawaidollshop.